Demographic change, growth and agglomeration - Theresa Grafeneder-Weissteiner (European Regional Science Association (ERSA), 2010)
Recently, there has been wide interest in the "economics" of population aging. Demographic change has crucial consequences for economic behavior; it e.g. implies that consumption and investment decisions vary over the life-cycle. The latter has important implications for economic growth, whereas the former is decisive for the location of economic activity as emphasized in the New Economic Geography (NEG) literature. Both growth and agglomeration processes are, however, themselves interlinked, since technological spillovers, being the engines of endogenous growth, are often localized. This linkage has inspired the development of frameworks that combine (endogenous) growth features with NEG models to study the joint process of creation and location of economic activity. All these models focus, however, on the consequences of increased economic integration while ignoring any potential effect of demographic change. This paper closes the gap by incorporating an overlapping generation structure into Baldwin (2001) 's NEG model with learning spillovers and thus allows to investigate how lifetime uncertainty impacts upon growth and agglomeration. The main results are twofold. First, nonzero mortality rates support a more equal distribution of productive factors by introducing an additional dispersion force that countervails the agglomeration tendencies resulting from endogenous growth through localized knowledge spillovers. For sufficiently high interregional knowledge spillovers, the turnover of generations can even prevent regions from unequal development. Moreover, lifetime uncertainty considerably reduces the possibility of agglomeration being the result of a self-fulfilling prophecy. Second, nonzero mortality rates lower both the symmetric equilibrium's as well as the core-periphery's growth rate. As long as learning spillovers are not purely localized, this decrease is, however, more pronounced for the core-periphery outcome. Thus, in sharp contrast to standard NEG findings, agglomeration is not necessarily conducive to growth. This also implies that there might not be any trade-off between fostering an equal distribution of productive factors and high economic growth which would result from e.g. increased economic integration if agglomeration were unambiguously pro-growth. Baldwin, R. E., Martin, P., and Ottaviano, G. I. P. (2001). Global income divergence, trade, and industrialization: The geography of growth take-offs. Journal of Economic Growth, 6:5-37.
Keywords: F43; O33; J10; R11; 330; Agglomeration; Endogenous Growth; Demographic Change; Knowledge Spillovers